ISLAM DAN ETIKA PLURALISME - Faisar Ananda Arfa (State Islamic University North Sumatra, 2011)
Abstract: Islam and the Ethics of Pluralism. One of the most important issues that reemerge in the globalized era is pluralism. In Isalm, since the beginning of its days acknowledges and even practice living in plurality. The prophet Muhammad has introduced this atmosphere since he moved to Medina where the Muslims constituting the Muhajirin and Anshar living together in harmony the Jews and Christians who had been living for quite a long time. This article is aimed at exploring some principles of Islam regarding pluralism as well as analyzing how this concept has become a significant element in modern world.Kata Kunci: Islam, etika pluralisme